INNER CONFLICT OF SULEYMAN IN MOVIE AYLA, THE DAUGHTER OF WAR - Oktaviani, Yesi; Ramdhani, Muhammad Iqbal (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
The objectives of this study is to analyze the movie by using Sigmund Freud Theory. This study aims to find out the inner conflict or Psychological aspects of the main characterâ€™s, Suleyman in the movie â€œAyla the Daughter of Warâ€. This study used descriptive method. The data were collected through utterances of major character which indicates inner conflict. The results show that there are 15 Id, and 17 Superego. In this movie, Suleymanâ€™s character is dominated by Superego, and The ego on the Suleyman character as a determinant of the Superego and Id. In accordance with the findings, the writers would like to suggest to further writers in choosing the movie which has the characters that suitable for the theory of psychoanalysis by Sigmund Freud.